Polyimide Based-Carbon Membrane: Effect of Pyrolysis Environment - Norazlianie, Sazali; Ramli, Junid; Siregar, J. P. (Penerbit Akademia Baru, 2020)
Tubular carbon membrane was prepared from BTDA-TDI/MDI (P-84) polyimide as a main precursor that blends with nanocrystalline cellulose (NCC) through controlled pyrolysis condition. The effects of the final pyrolysis environment on